Health and social organization : towards a health policy for the twenty-first century (London, 2000)
"There is a growing recognition that the most powerful determinants of health in modern populations are to be found in social, economic and cultural circumstances. Health and Social Organisation focuses on the determinants of health in developed countries, discussing the role of education, the workplace and the family. It considers the timing of major influences on health and questions whether there are special periods of vulnerability early in life or whether circumstances throughout life are equally important. The final section draws out the implications for policy and for links between health and economic performance, emphasizing the need for greater investment to combat the low educational standards and high unemployment which cause both poor health and poor economic performance."